A Komunitas Pembangunan Afrika Selatan penerapan Keamanan Kolektif Melawan Teroris Al Sunnah di Mozambik (2015 - 2021) - Willie Mandigo; Makarim Wibisono; Budi Pramono (International Journal Of Humanities Education and Social Sciences (IJHESS), 2023)
Beginning on October 5, 2017, Al Sunnah militants in the Cabo Delgado region of Mozambique violently attacked security personnel, governmental buildings, and the civilian public and by 2020 the terrorists had killed more than 3,000 people and driven almost 800,000 people from their homes. The terrorists were also starting to spill over into neighboring nations creating a regional security threat. The Mozambique security forces reacted to the situation without success as the reaction force was underequipped and lacked the necessary skills. As the situation further worsened, Mozambique requested the Southern African Development Community for assistance on the basis of the group’s collective security provisions. This culminated in the deployment of the SADC Mission in Mozambique (SAMIM). This study aims at evaluating the collective defense capacity-building initiatives adopted by SADC to assist Mozambique. The study uses a qualitative approach with data gathered through document analysis and interviews of 15 purposely selected informants comprised of military officers directly involved in the conflict, academics and key politicians. Collective security initiatives adopted by SADC include diplomatic involvement, training, offensive military operations, the provision of military gear, guidance, funding, consulting services, and intelligence services. The outcomes show that, despite certain difficulties, the collective initiatives by SADC member states were sufficient to achieve the desired end state of neutralizing the Al Sunnah terrorists and restoring peace and security to Cabo Delgado Province.